Simultaneous determination of benzodiazepines in whole blood or serum by HPLC/DAD with a semi-micro column - El Mahjoub, Anissa; Staub, Christian (Journal of pharmaceutical and biomedical analysis, 2000)
A simple and sensitive high performance liquid chromatographic (HPLC) method using a semi-micro column, C 8 reversed-phase column (3 mm i.d.) and a low flow rate 0.3 ml/min was developed and validated for the determination of five frequently prescribed benzodiazepines: clonazepam, diazepam, flunitrazepam, midazolam and oxazepam. Quantification was performed at 220 nm with methylclonazepam as internal standard. The method involved a simple extraction from alkalinized blood (1 ml) into 1-chlorobutane and provided excellent sensitivity, recovery, accuracy and reproducibility for benzodiazepines in therapeutic or toxic concentrations.